Functional properties of a Drosophila homolog of the E2F1 gene. - Ohtani, K (1994)
A variety of studies have now implicated the cellular transcription factor E2F as a key participant in transcription control during the cell growth cycle. Although the recent isolation of molecular clones encoding proteins that are components of the E2F activity (E2F1 and DP-1) provides an approach to defining the specific involvement of E2F in these events, definitive experiments remain difficult in the absence of appropriate genetic systems. We have now identified a Drosophila equivalent of E2F1 that we hope will allow an eventual genetic approach to the role of E2F in cellular regulatory events. A cDNA clone was isolated from a Drosophila cDNA library by using a probe containing sequence from the E2F1 DNA binding domain. The sequence of the clone, which we term drosE2F1, demonstrates considerable homology to the human E2F1 sequence, with over 65% identity in the DNA binding region and 50% identity in the region of E2F1 known to interact with the retinoblastoma gene product. A glutathione S-transferase-drosE2F1 fusion protein was capable of binding specifically to an E2F recognition site, and transfection assays demonstrated that the drosE2F1 product was capable of transcription activation, dependent on functional E2F sites as well as sequences within the C terminus of the protein. Finally, we have also identified E2F recognition sequences within the promoter of the Drosophila DNA polymerase alpha gene, and we demonstrate that the drosE2F1 product activates transcription of a test gene under the control of this promoter. We conclude that the drosE2F1 cDNA encodes an activity with extensive structural and functional similarity to the human E2F1 protein.